KONTRIBUSI KUALITAS JASA, KEPERCAYAAN DAN KEPUASAN KONSUMEN DALAM MENCIPTAKAN LOYALITAS KONSUMEN - Erwin Erwin; Tumpal J. R Sitinjak (Business Management Journal, 2017)
This study aims to examine the contribution of influence quality of service, trust, and consumer satisfaction in creating consumer loyalty.The object of this research is JNE Apartment Gading Nias. This study used a causal study using a questionnaire for data collection. For sampling, the method used is non probability sampling with judgment sampling technique The procedure used for model testing and data processing is the structural equation modeling using Linear Structural Relationship (Lisrel) method through software Lisrel 8.80.This research resulted the finding that the service quality have positive and significant effect to the trust, the quality of service have positive and significant effect to the consumer satisfaction, the quality of service have positive and significant influence to consumer loyalty, trust not influence to consumer loyalty, and consumer satisfaction have positive and significant influence to loyalty consumer.Keywords: Service Quality, Trust, Consumer Satisfaction, Consumer Loyalty